Morningness‐eveningness and educational outcomes: the lark has an advantage over the owl at high school. (3rd January 2012) - Preckel, Franzis; Lipnevich, Anastasiya A.; Boehme, Katharina; Brandner, Lena; Georgi, Karsten; Könen, Tanja; Mursin, Katharina; Roberts, Richard D.
Abstract : Background. Chronotype refers to individuals' preference for morning or evening activities. Its two dimensions (morningness and eveningness) are related to a number of academic outcomes. Aims. The main goal of the study was to investigate the incremental validity of chronotype as a predictor of academic achievement after controlling for a number of traditional predictors. In so doing, a further aim was ongoing validation of a chronotype questionnaire, the Lark‐Owl Chronotype Indicator. Sample. The sample comprised 272 students attending 9th and 10th grades at five German high schools. Data was also obtained from 132 parents of these students. Method. Students were assessed in class via self‐report questionnaires and a standardized cognitive test. Parents filled out a questionnaire at home. The incremental validity of chronotype was investigated using hierarchical linear regression. Validity of the chronotype questionnaire was assessed by correlating student ratings of their chronotype with behavioural data on sleep, food intake, and drug consumption and with parent ratings of chronotype. Results. Eveningness was a significant (negative) predictor of overall grade point average (GPA), math–science GPA, and language GPA, after cognitive ability, conscientiousness, need for cognition, achievement motivation, and gender were held constant. Validity evidence for the chronotype measure was established by significant correlations with parent‐ratings and behavioural data. Conclusions. Results point to the possible discrimination of adolescents with a proclivity towards eveningness at school. Possible explanations for the relationship between chronotype and academic achievement are presented. Implications for educational practice are also discussed.